Can Perceived Usefulness and Online Experiences Affect ShopeePay Fintech Usage by Millennial Muslims? - Aisyiah, Helti Nur; Prastiwi , Septi Kurnia; Rohimat, Asep Maulana (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
Financial Technology (Fintech) has been embedded in the community, especially to support their economic activities. The fintech usage provides convenience, so that users are increasingly widespread. This study aims to determine the effect of perceived usefulness and online experiences on the fintech usage with trust as a mediating variable. This study used a quantitative approach by distributing questionnaires to 102 millennial Muslims in Solo Raya. Questionnaires filled out by participants were processed using the IBM SPSS Statistics Version 26. The results showed that perceived usefulness had an effect on fintech usage, while online experiences had no effect on fintech usage. Among perceived usefulness, online experiences, and fintage usage, there was trust. However, trust could not mediate between perceived usefulness and online experiences on the fintech usage. This research will contribute to fintech developers in managing their technology by taking into account perceived usefulness, online experiences, and trust factors.